A neuroreabilitação de pacientes pós acidente vascular encefálico na terapia por contensão induzida - MIRANDA, Izabelle Cristina da Cruz (2023)
Stroke is defined as a sudden neurological deficit due to a restriction in the blood supply causing encephalon lesions. Currently 90% of the survivors develop some type of disability, which causes dificulties in the subject´’s activity daily life performance, making stroke the greatest cause of disability in the world. Constraint-Induced Movement Therapy (CIMT) is a therapy that aims to recover paretic upper limb’s (UL) function of the of patients with stroke sequelae through intensive training and restriction of non-paretic UL during 90% of the day. Intensive training occurs through motor activities related to the subject’s context and, consequently, related to the areas of occupational performance such as activity daily life, leisure and productive activities. The present study aims to analyze the effects of CIMT on the functional capacity of individuals after stroke, using Wolf Motor Function Test (WMFT), Motor Activity Log (MAL) and Canadian Occupational Performance Measure (COPM), presenting a qualitative-descriptive approach, with pre-test / post-test comparision and a self control analysis. Four participants will be submited to the therapeutic program. The sessions will occur five times a week, lasting three hours and will be located in Universidade Federal do Pará. The data will be presented in graphs or tables, however, the analysis will be given qualitatively, describing and analyzing the scores obtained in the protocols in the evaluation and after ten sessions.